Perbedaan Pengetahuan Ibu Hamil Sebelum Dan Sesudah Diberikan Edukasi Video Hipotiroid Kongengital: Ibu hamil, edukasi, hipotiroid kongengita - Astuti, Ni Made Wiwik; Erny Astiti, Ni Komang; Somoyani, Ni Ketut (JURNAL KEBIDANAN, 2025)
Congenital hypothyroidism (HK) is one of the preventable causes of mental retardation in children if recognized and treated early. Congenital hypothyroidism causes overall physical growth impairment, and the worst is mental retardation. The coverage of congenital hypothyroid screening in Kediri III Health Center is 95.5%. The purpose of the study in general to determine the difference in knowledge of pregnant women before and after being given video education. This study a pre-experimental with a one group pretest-posttest design. The sampling technique used was purposive sampling technique. The sample formula used is paired numerical comparative with the number of samples obtained is 22 respondents. This research was conducted at Kediri III Health Center from April-May. The type of data is primary data obtained with a questionnaire that has been tested for validity and reliability. The mean pretest result is 64.23, the mean posttest is 87.41. The mean increase was 23.18. The data normality test uses Saphiro-wilk with the results of data not normally distributed, so the bivariate analysis uses the Wilcoxon test with the results of p value = 0.000 <0.05, with a Positive Rank of 22 meaning that all respondents in this study experienced an increase in value after being given the intervention. Suggestions are given that midwives provide counseling with more informative and interactive media